Strategi Pembelajaran Diferensiasi dalam Pembelajaran PAI untuk Memenuhi Kebutuhan Heterogenitas Siswa - Furqon, Zenal; Nugraha, Mulyawan Shafwandy (Indonesia, 2024)
Abstract : The learning process is a conscious effort to change someone into a better condition, differentiation learning will be able to help to increase the level of success of graduates or someone's learning outcomes, because the differentiation process will make students learn according to their wishes and wishes which will later lead to interest. and his talents. Heterogeneity is also a necessity if we look deeper into the students in our schools, therefore differentiation strategies in learning are very good to be able to implement. PAI learning does not escape the heterogeneity of students in each class, so that differentiation in learning will be able to increase success in achieving PAI learning goals. Keywords : differentiation, heterogeneity, learning, PAI